RELEVANCE OF REALISM IN THE CONTEMPORARY EDUCATIONAL SYSTEM - Swaroopa.P.K; Aadil Hussain Mir (RADJA PUBLIKA, 2024)
Realism remains a prominent educational philosophy in contemporary educational systems, emphasizing the objective existence of reality and the importance of empirical evidence in knowledge acquisition. Originating from the works of ancient philosophers and evolving through figures like John Dewey and Jean-Jacques Rousseau, realism advocates for a curriculum grounded in factual knowledge across disciplines such as mathematics, sciences, and history. In today’s educational landscape, realism informs teaching practices that prioritize critical thinking, problem-solving skills, and practical application of knowledge. This philosophy integrates advancements in technology, promoting experiential learning through digital tools and interactive simulations. However, realism faces challenges, including criticisms of its potential to overlook creativity, cultural diversity, and ethical considerations in education. Addressing these concerns requires a balanced approach that combines realism with inclusive educational practices and interdisciplinary learning. Moving forward, realism continues to shape educational policies and pedagogical strategies, aiming to prepare students for global citizenship and lifelong learning in a rapidly evolving world